Leukocyte Count and Neutrophil/Lymphocyte Ratio as Predictor of Mortality in Sepsis Patients - Sotianingsih Sotianingsih; Samsirun Halim; Ahmad Syauqi; Lidia Teresia Sinaga; Michelle Gracella (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Mortality in septic patients remains high despite much progress in understanding the definition, pathophysiology, and management of sepsis through sepsis bundles. Both leukocyte count and Neutrophil/Lymphocyte Ratio (NLR) are relatively inexpensive routine tests for infectious patients. Several studies of leukocytes, total neutrophils, total lymphocytes, and neutrophil/lymphocyte ratio were carried out as alternative parameters for monitoring the severity and as prognostic factors. This study aimed to analyze the difference in leukocytes and NLR based on the outcome of sepsis patients and evaluate their role in predicting death. The study was an analytic cohort of sepsis patients in intensive care at Raden Mattaher Hospital Jambi as the subjects. The research variables were survivor and non-survivor outcomes, leukocyte count, and NLR evaluation at 0, 24, 72, and 144 hours. Data were analyzed using the SPSS 21 test of difference and survival test. There was a total of 34 subjects, which consisted of a group of survivors of 14 patients (41.18%) and non-survivors of 20 patients (58.82%). At the initial diagnosis of sepsis, there was a statistically significant difference in the leukocyte count (p=0.006) and NLR (p=0.042) between survivors and non-survivors. At initial diagnosis, the leukocyte count > 15.49 X 103/µL can predict the death of sepsis patients with a Hazard Ratio (HR) of 4.001. The survival rate of patients with a leukocyte count < 15.49X103/µL and > 15.49 X 103/µL was 89.4% and 64.3%, respectively, which was statistically significant (p=0.0002). At initial diagnosis, NLR with a value of> 13.2 can predict the death of sepsis patients with HR 3.370 (p=0.001). Leukocyte count > 15.49 X 103/µL and NLR > 13.2 at the initial diagnosis of sepsis showed a risk of death of 4.001 and 3.370 times higher risk in the 144-hour evaluation. Leukocyte count > 15.49 X 103/µL and NLR > 13.2 was able to be a predictor of mortality and an indicator of a need for aggressive management in sepsis patients.